THE RELATIONSHIP BETWEEN PARENTING PATTERNS, KNOWLEDGE AND IMMUNIZATION WITH THE INCIDENCE OF STUNTING IN TODDLERS IN THE WORK AREA OF SANGGIRAN COMMUNITY HEALTH CENTER, SIMEULUE REGENCY IN 2024 - Ninis Annisa; Marniati; Suci Eka Putri (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Stunting is a failure of growth and development in months and toddlers agen 12-59 years chronic malnutrition especially in the first 1,000 days of life, which can be characterized by height that is not in accordance with age <-2 SD based on the Z-Score table. The problem in this study is high rate of stunting in the last 3 years at the Sanggiran Health Center, namely in 2022 the number of stunted toddlers reached 58 people (13), in 2023 the number of stunted toddlers increased to 81 people (20%), in 2024 the number of stunting decreased to 41 people (11%). The purpose of this study was to see the relationship between parenting patterns, knowledge of stunting and immunization with the incidence of stunting in toddlers in the Sanggiran Health Center Work Area, Simeulue Regency In 2024. The research design used is cross-sectional. The population in this study were all stubted toddlers in the Sanggiran Health Center Working Area in 2024 and the number of samples in this study was 41 people. Data analysis using SPSS application with Chi-square statistical test significance value 95%. The results of this study indicate that there is a relationship between maternal parenting patterns and stunting incidence (P=0,000). This study reveals a significant correlation between immunization status and stunting (P=0.036), as well as between knowledge level and stunting (P=0.018). The conclusion is that there is a relationship between parenting patterns, immunization, knowledge, and Stunting In The Sanggiran Health Center Work Area in 2024. Suggestions for further researchers can improve variables such as economic status, energy intake, and drinking water sources.